THE EFFECTIVENESS OF THE PHYTOMEDICINE IN THE TREATMENT OF THE PATIENTS WITH THE CHRONIC NONBACTERIAL PROSTATITIS - Литвинець, Є. А.; Литвинець, В. Є.; Сандурський, О. П.; Тріщ, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The aim of the working was the study of the effectivenes and the prevention of using the phytomedicine Ambovit in the treatment of patients with the chronic nonbacterial prostatitis. We was analysed the aspects of ethiopathogenesis of chronic nonbacterial prostatitis. We was studied the results of treatment of 65 patients with these pathology. The patients were divided on the two groups: 1- received the standart therapy during 1 month , 2- plus + Ambovit in doses 20 drops or 1 tablets for three times a day. The analysis of the results of the treatment demonstrated that the using of the Ambovit for helps to achieve the best results and clinical effect in patients of second group.